1979
DOI: 10.1063/1.437694
|View full text |Cite
|
Sign up to set email alerts
|

Thermal rate constants, energy dependence, and isotope effect for halogen–hydrogen halide reactions

Abstract: Thermal rate constants have been determined for the reaction C1+DI and Br+HI in the temperature range 220–400 K. For C1+DI, the effective reaction cross section reaches a maximum of 18.8 Å2 near 345 K. The isotope effect increases in favor of HI from 1.5 to 2.7 as the temperature decreases from 400 to 223 K. For Br+HI, the effective reaction cross section decreases slightly with increasing temperature. The cross section at enhanced collisional energy, with various rotational energies, is determined for the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In addition, the ratio of rate coefficient for Cl atoms with HI and DI also showed a pronounced temperature dependence and an increase in the translational energy of the Cl atom reduced the rate coefficient. These results were interpreted in terms of a complex reaction mechanism in which the Cl atoms is first attracted to the I end of HI prior to a H rotation to give the HCl and I products . Vibrational excitation in OH may lead to similar effects.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the ratio of rate coefficient for Cl atoms with HI and DI also showed a pronounced temperature dependence and an increase in the translational energy of the Cl atom reduced the rate coefficient. These results were interpreted in terms of a complex reaction mechanism in which the Cl atoms is first attracted to the I end of HI prior to a H rotation to give the HCl and I products . Vibrational excitation in OH may lead to similar effects.…”
Section: Discussionmentioning
confidence: 93%
“…Such deviation is usually indicative of a complex mechanism involving two or more concurrent chemical reactions. The authors 9 interpret it instead as a dynamic process coming from attractive attack of Cl on the Br end of HBr followed by rapid bending or tunneling, or both, of the H atom to form the product HCl + Br. They suggested that the direct attack of Cl on the H atom in HBr would have a different rate.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction rate for v = 2 is approximately four orders of magnitude larger than for v = 0. The Cl + HI reaction cross section versus temperature peaks at 30Å 2 near 330 K, and the cross section for hot Cl with 11.4 kcal mol −1 of relative translational energy is nine times smaller than thermal at 295 K. The hot atom cross section increases by 25% as temperature increases from 223 to 295 K. These data suggest that the dynamics of relative translational motion is controlled by an attractive potential that brings Cl and I together (ClIH), and the reaction completes by hydrogen rotating around over a modest barrier to connect with the Cl (89,93 (70,94,95) (Figure 6). …”
Section: Bimolecular Reactionsmentioning
confidence: 92%
“…Understanding such reactions and relaxations has been critical for the production and maintenance of inverted vibrational populations in chemical lasers. Glenn Macdonald, Steve Leone, Klass Bergmann, and Chang-Chi Mei carried out a series of measurements of halogen + hydrogen halide reaction and relaxation rates (64)(65)(66)(67)(68)(88)(89)(90)(91)(92)(93) because for HCl(v = 2, 1), the total energy is well above the barrier to Cl + OH formation (68, 69). Figure 5 shows the main results: Most (probably two-thirds to three-fourths) of the HCl(v = 2) is relaxed to v = 1 rather than reacting to give OH.…”
Section: Bimolecular Reactionsmentioning
confidence: 99%